A label-free electrochemical impedance aptasensor for cylindrospermopsin detection based on thionine–graphene nanocomposites. Issue 16 (21st August 2015) - Zhao, Zhen; Chen, Hongda; Ma, Lina; Liu, Dianjun; Wang, Zhenxin
<x xml:space="preserve">Abstract</x> A simple and effective label-free electrochemical impedance aptasensor based on thionine–graphene nanocomposites has been fabricated for cylindrospermopsin (CYN) determination.